KONFIGURASI POLITIK DALAM PEMBENTUKAN HUKUM PERBANKAN SYARIÔÇÖAH - Bakhtiar, Bakhtiar (Alfuad: Jurnal Sosial Keagamaan, 2019)
Sharia banking law was formed in the reform era through the procedure of making political decisions at the suggestion of the DPR RI. At the beginning of the reform order the legal product tended to be responsive. All the pillars of democracy can play a role. It’s just that legal products that are born more serve international institutions or financiers because political configurations are more likely to be oligharkhi-cartels. The birth of this law is in line with the increasingly existence of Islamic banking in contributing and economic growth in Indonesia. As a political product, sharia banking law was born after a number of fundamental changes, especially changes in the construction of judicial authority carried out by the Supreme Court and the Judiciary under it. The birth of Islamic banking law follows a responsive legal character because this law embodies the needs of the community, guarantees business certainty and guarantees legal protection, gives space and movement to Islamic banking to develop and create innovations in Islamic banking products and services. In addition, this law is also the answer to the implementation of laws in accordance with Pancasila and has accommodated the needs of religious law. In the process of forming all stakeholders play an active role in either political parties or political forces, community organizations, government and society.